Characteristics and behaviour of African factor markets and market institutions and their consequences for growth (1999)
This paper provides a detailed characterisation of the structure and behaviour of African factor markets and the institutions that impact on their operations. It shows that the African factor markets are imperfect and inefficient, thus constraining economic growth. The paper posits that for the current reform programmes to succeed, policy that enhances the efficiency and competitiveness of the African factor markets must be put in place.